L-Ornithine L-Aspartate Restores Mitochondrial Function and Modulates Intracellular Calcium Homeostasis in Parkinson’s Disease Models - Maria Josè Sisalli; Salvatore Della Notte; Agnese Secondo; Carmelo Ventra; Lucio Annunziato; Antonella Scorziello (Cells, 2022)
The altered crosstalk between mitochondrial dysfunction, intracellular Ca2+ homeostasis, and oxidative stress has a central role in the dopaminergic neurodegeneration. In the present study, we investigated the hypothesis that pharmacological strategies able to improve mitochondrial functions might prevent neuronal dysfunction in in vitro models of Parkinson’s disease. To this aim, the attention was focused on the amino acid ornithine due to its ability to cross the blood–brain barrier, to selectively reach and penetrate the mitochondria through the ornithine transporter 1, and to control mitochondrial function. To pursue this issue, experiments were performed in human neuroblastoma cells SH-SY5Y treated with rotenone and 6-hydroxydopamine to investigate the pharmacological profile of the compound L-Ornithine-L-Aspartate (LOLA) as a new potential therapeutic strategy to prevent dopaminergic neurons’ death. In these models, confocal microscopy experiments with fluorescent dyes measuring mitochondrial calcium content, mitochondrial membrane potential, and mitochondrial ROS production, demonstrated that LOLA improved mitochondrial functions. Moreover, by increasing NCXs expression and activity, LOLA also reduced cytosolic [Ca2+] thanks to its ability to modulate NO production. Collectively, these results indicate that LOLA, by interfering with those mitochondrial mechanisms related to ROS and RNS production, promotes mitochondrial functional recovery, thus confirming the tight relationship existing between cytosolic ionic homeostasis and cellular metabolism depending on the type of insult applied.